Quantifying the inclusion of cardiovascular research into clinical guidelines - Johan Skov Bundgaard; Jonas Skjold Raaschou-Pedersen; Kasper Iversen; Henning Bundgaard; Mark P. Khurana; Daniel Raaschou-Oddershede (Clinical Research in Cardiology, 2026)
Abstract Background The number of cardiovascular research articles is growing rapidly, but the subsequent incorporation into newer guidelines remains uncertain. We aimed to quantify the proportion of topic-relevant literature published between consecutive European Society of Cardiology (ESC) guideline editions that was cited in the later edition. Methods Using PubMed Medical Subject Heading (MeSH) searches and OpenAlex citation graphs, we identified all publications published between two ESC guideline editions across eight topics. We quantified the proportion of inter-guideline publications that were cited in the subsequent guideline. Results Across the eight topics, a mean of 2.2% (SD = 2.0) of inter-guideline publications were directly cited in the successive guideline. Clinical trials were more frequently cited than non-clinical trial publications (8.5% [SD = 6.8] vs 2.0% [SD = 2.0]) in a topic-adjusted logistic regression; the odds were roughly fivefold higher (OR 5.45, 95% CI 4.87–6.10). Conclusions ESC guidelines cite a small proportion of the cardiovascular literature published since their preceding edition, drawing disproportionately on clinical trials.